2015
DOI: 10.1016/j.astropartphys.2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Cosmogenic activation of a natural tellurium target

Abstract: 130Te is one of the candidates for the search for neutrinoless double beta decay. It is currently planned to be used in two experiments: CUORE and SNO+. In the CUORE experiment TeO2 crystals cooled at cryogenic temperatures will be used. In the SNO+ experiment natTe will be deployed up to 0.3% loading in the liquid scintillator volume. A possible background for the signal searched for, are the high Q-value, long-lived isotopes, produced by cosmogenic neutron and proton spallation reaction on the target materia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…As shown in the excitation functions plotted in Ref. 81 for 110m Ag and 60 Co, the measured cross sections above 800 MeV agree reasonably well with predictions of ACTIVIA; the origin of the difference can be at lower energies (the region giving the dominant contribution to the production rates). The different cosmic neutron spectra considered in the two works makes difficult also the comparison.…”
Section: Telluriumsupporting
confidence: 69%
See 2 more Smart Citations
“…As shown in the excitation functions plotted in Ref. 81 for 110m Ag and 60 Co, the measured cross sections above 800 MeV agree reasonably well with predictions of ACTIVIA; the origin of the difference can be at lower energies (the region giving the dominant contribution to the production rates). The different cosmic neutron spectra considered in the two works makes difficult also the comparison.…”
Section: Telluriumsupporting
confidence: 69%
“…), was analyzed in Ref. 81. For long-lived isotopes, the underground activation was estimated to be less than 1 event/(y t).…”
Section: Underground Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Production rates (in µBq kg −1 ) at sea level presented in Ref 79. for isotopes induced in TeO 2 combining measured cross sections at different energies and in Ref 81. for natural tellurium using ACTIVIA and TENDL library.…”
mentioning
confidence: 99%
“…The purification system for the surfactant and the telluric acid is currently under development. A detailed study of the production of possible backgrounds by cosmogenic activation on Tellurium [3] showed that a purification factor of 10 4 followed by a 3 to 6 months cool-down is needed for the telluric acid. This will be achieved by a 2-stage re-crystallization purification procedure.…”
Section: Lab Purification and Backgroundsmentioning
confidence: 99%